2020
DOI: 10.4103/ijt.ijt_25_20
|View full text |Cite
|
Sign up to set email alerts
|

Scalp hair whorl patterns in patients affected by Neurofibromatosis Type 1: A case-control study

Abstract: Background: The hair whorl denotes the spiral disposition of hairs around an axis, which is determined by the follicle growing direction. Atypical variants of scalp hair patterns, identified by abnormally placed or multiple whorls, have been associated with early brain developmental disorders and several dysmorphic syndromes. Materials and Methods: A 6-month case–control, prospective monocentric study included an overall number of 557 children. A logistic regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Breeders' preference for animals with a certain shape, number and location of hair whorls may have some scientific legitimacy and is not entirely baseless. Studies found an association between shape and position of hair whorls with genes, heredity, cognisance, temperament, brain development, health conditions and sexuality, in cattle (Craft and Warner, 1934;Deesing, 2020), dogs (Lillebo, 2014;Tomkins and McGreevy, 2010), horses (Cruz et al, 2021;Encina et al, 2023), swine (Craft and Warner, 1934) and human beings (Aksu et al, 2013;Csabi et al, 2014;Kiil, 1948;Klar, 2005;Luo et al, 2023;McDonald, 2011;Ruiz-Maldonado, 2002;Sechi, et al, 2020;Smith and Gong, 1973;Smith and Gong, 1974;Tirosh et al, 1987). Studies found that cattle with hair whorls above the eyes are more agitated during restraint (Grandin et al, 1995), and in the auction ring (Lanier et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Breeders' preference for animals with a certain shape, number and location of hair whorls may have some scientific legitimacy and is not entirely baseless. Studies found an association between shape and position of hair whorls with genes, heredity, cognisance, temperament, brain development, health conditions and sexuality, in cattle (Craft and Warner, 1934;Deesing, 2020), dogs (Lillebo, 2014;Tomkins and McGreevy, 2010), horses (Cruz et al, 2021;Encina et al, 2023), swine (Craft and Warner, 1934) and human beings (Aksu et al, 2013;Csabi et al, 2014;Kiil, 1948;Klar, 2005;Luo et al, 2023;McDonald, 2011;Ruiz-Maldonado, 2002;Sechi, et al, 2020;Smith and Gong, 1973;Smith and Gong, 1974;Tirosh et al, 1987). Studies found that cattle with hair whorls above the eyes are more agitated during restraint (Grandin et al, 1995), and in the auction ring (Lanier et al, 2001).…”
Section: Resultsmentioning
confidence: 99%